Frequency-multiplexed tunable logic device based on terahertz graphene-integrated metamaterial composed of two circular ring resonator array - Somayyeh Asgari; Tapio Fabritius (Scientific Reports)
Abstract This paper presents a novel terahertz (THz) graphene-based tunable metamaterial that operates as a frequency-multiplexed logic device. The structure consists of a gold layer, a dielectric substrate, and an array of graphene resonators formed by two circular ring resonators per unit cell. The metamaterial is simulated and designed in CST Software. The equivalent circuit model (ECM) for the metamaterial is obtained using MATLAB code. Logical input values are set by adjusting the Fermi levels of graphene-based circular resonators, while output logic states are determined by analyzing the reflection spectrum. The proposed device operates within the THz range, enabling the realization of OR, XNOR, and NAND logic gates at three distinct frequencies. Additionally, the working frequencies of these gates can be tuned by modifying the graphene’s Fermi level. The highest extinction ratios (ERs) achieved for the OR, XNOR, and NAND gates are 36.93, 65.66, and 22.38 dB, respectively. Owing to its simple design and versatility, this metamaterial shows strong potential for use in THz digital systems.